ORAL LICHEN PLANUS LESION MIMICKING LINEAR GINGIVAL ERYTHEMA : A CASE REPORT - Indra Gunawan; Tenny Setiani Dewi (Journal of Syiah Kuala Dentistry Society, 2017)
Oral lichen planus (OLP) is a chronic inflammatory disease that affects the mucous membrane of the oral cavity. It is a T-cell mediated autoimmune disease in which the cytotoxic CD8+ T cells trigger apoptosis of the basal cells of the oral epithelium. Linear Gingival Erythema (LGE) is a progressive disease described in HIV-positive patients and is considered to be an early stage of necrotizing periodontitis. Objective of this case report is to help clinicians to recognize and distinguish OLP lesions from other lesions that have similar appearance such as LGE and give a proper treatment for the oral lesions. We reported a case on a 49-year-old female that was referred to Oral Medicine Department from Periodontology Department with the diagnosis of ANUG and differential diagnosis of Linear Gingival Erythema. On clinical examination, we found Wickhams striae on buccal mucosa and the edge of the lesion. The patients was then diagnosed with Oral Lichen Planus. The patient was treated with sistemic and topical corticosteroid. After 8 weeks of treatment the patient was fully recovered. OLP is seen clinically as reticular, papular, plaque-like, erosive, atrophic or bullous types. Intraorally, the buccal mucosa, tongue and the gingiva are commonly involved although other sites may be rarely affected. Erosive or atrophic types that usually affect the gingiva usually show concomitant reticular form. LGE is limited to the soft tissue of periodontium and characteristically appears as an erythematous linear band that extends approximately 2 3mm from the free gingival margin. OLP lesions may have similarity with other oral lesions such as LGE. It is important for clinicians to recognize the lesions and choosing the proper treatment for the diseasesKeyword: Oral Lichen Planus, Linear Gingival Erythema, HIV, Corticosteroid